Especially the location of segments atmosphere where total ozone changing is connected with variations of the surface temperature in the gulf of Alasks of Pacific ocean - Холопцев, А. В.; Ларченко, И. А. (Man and Environment. Issues of Neoecology, 1970)
In features the location of the segments an atmosphere, which the interannual changes in CCA statistically significantly associated with the same time variations surface temperature of the Pacific Ocean Gulf of Alaska. The influence of seasonal factors. The adequacy of representations the impact on air exchange between troposphere and stratosphere and the planetary gravitational waves, that form over areas of interaction of jets with inhomogeneities of the atmospheric pressure field which are destroyed in tropopause and stratosphere.